Factors affecting buying decisions of Islamic banking products: the moderating role of religious belief - Nizar Al-Malkawi, Husam-Aldin (2023)
Purpose–Thepurposeofthisstudyistoexaminetheimpactofthemarketingmix,customerperceptions,and religion on the buying decision of Islamic banking products in an emerging market namely the United Arab Emirates (UAE). Design/methodology/approach– This study adopts a quantitative approach to analyze the data of 435 respondents collected through an online survey during January–February 2022. Data analysis of direct and moderating relationships are done through Smart PLS (partial least squares) using structural equation modelling (SEM) technique. Findings– The results indicate that marketing mix (product, price, place and promotion) and customer perceptions have a positive direct relation with the buying decision of Islamic banking products in the UAE. However, moderation analysis shows that religion is a non-significant moderator for the above relationships. Originality/value– This study combines potential variables from the perspectives of marketing, human mindset, and individual beliefs. The findings of this study provide a wider understanding of consumer behavior toward Islamic banking products. Marketers of the Islamic banking industry can utilize these findings for effective market segmentation and well-crafted marketing strategies. This will ultimately contribute to the sustainable growth and development of the Islamic banking industry in the UAE and other regions.